The application of Internet of things and Oracle database in the research of intelligent data management system (Informatica, 2022)
Aiming at the needs of general large-scale monitoring systems, this paper designs an intelligent data management system that can provide fast data query and relieve sudden data congestion through in-depth research on Oracle database and data division. To the data access request from the front desk, the system can respond quickly through the real-time data monitoring module and the online analysis software OLAP mode database, which has far-reaching significance for the development of the Internet of Things and related systems. The experimental results show that, compared with the traditional system, the same bitmap index only occupies about 1/30 of the original table, and the data size is reduced by more than 10 times. The experimental data verifies the characteristics of the system in this paper to strengthen the background data receiving and processing capabilities, and alleviate the problems such as the reduction of the system running rate and even the system paralysis caused by the sudden mass data.